Pengaruh Pelapisan Akrilik terhadap Kualitas Papan Partikel dari Limbah Batang Kelapa Sawit - Merry Cristin Natalia Simaremare; Tito Sucipto; Lutfhi Hakim (Program studi Kehutanan USU, 2015)
To reduce the waste of oil palm trunks can be done by changing oil palm trunks into particle board. One way to improve the quality of particle board is by doing coating treatment of acrylic. This study evaluated the best acrylic level in improving the quality of oil palm trunk particle board with isocyanate as the adhesive. Boards were made with size 25 cm x 25 cm x 1 cm with a target density of 0.7 g/cm3, felts temperature 160º and pressure 25 kg/cm2 for 3 minutes. Physical and mechanical properties were compared with SNI 03-2105-2006. The treatment variations were acrylic levels (0%, 5%, 10%, and 15%) with 3 repetitions. Results showed that the values of the density, moisture content, water absorption, thickness swelling, modulus of rupture, modulus of elasticity and internal bond were respectively 0,46-0,60 g/cm3, 10,52-11,01%, 5,32-55.35%, 2,37-6,40%, 26,45-60,87 kg/cm2, 2619,15-5092,82 kg/cm2 and 2,28-4,61 kg/cm2. All result values of physical properties testing except value of the moisture content achieved the standards of SNI 03-2105-2006. Instead, all result values of mechanical properties testing did not achieve the standards of SNI 03-2105-2006. The results showed that the particle boards with acrylic coating treatment has better quality than the particle boards without the acrylic coating treatment for the entire physical properties testing in addition to moisture content. Best acrylic level for the coating treatment of oil palm trunk particle board is 15%.